1992
DOI: 10.1126/science.1519066
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Neural Stereoscopic Processing in Primate Area V1 by the Viewing Distance

Abstract: Accurate binocular depth perception requires information about both stereopsis (relative depth) and distance (absolute depth). It is unclear how these two types of information are integrated in the visual system. In alert, behaving monkeys the responsiveness of a large majority of neurons in the primary visual cortex (area V1) was modulated by the viewing distance. This phenomenon affected particularly disparity-related activity and background activity and was not dependent on the pattern of retinal stimulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
103
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 162 publications
(110 citation statements)
references
References 15 publications
7
103
0
Order By: Relevance
“…We found evidence for a transfer of spatiotopic information between visual areas as indicated by both our behavioral and functional data. First, at the behavioral level, and in agreement with our previous report (Zimmermann et al, 2013), adaptation aftereffects were observed after a saccade was executed. Second, fMRI adaptation was shifted from one to the opposite hemisphere consistent with a transsaccadic information transfer of adapter activity (Duhamel et al, 1992).…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…We found evidence for a transfer of spatiotopic information between visual areas as indicated by both our behavioral and functional data. First, at the behavioral level, and in agreement with our previous report (Zimmermann et al, 2013), adaptation aftereffects were observed after a saccade was executed. Second, fMRI adaptation was shifted from one to the opposite hemisphere consistent with a transsaccadic information transfer of adapter activity (Duhamel et al, 1992).…”
Section: Discussionsupporting
confidence: 76%
“…This finding implies that neural adaption generated in the left hemisphere was interhemispherically transferred and became effective in the right hemisphere. This shift of neural adaption activity might result from an active process, which accounts for the behavioral spatiotopic aftereffects observed in this and previous studies (Melcher, 2005;Turi and Burr, 2012;Zimmermann et al, 2013). Although our adapter and our probe stimuli activated expectedly ventral areas, our retinotopic mapping analysis revealed that the shift of adapter activity occurred in dorsal visual area V3 and in higher areas visual, including V4 and VO.…”
Section: Spatiotopic Adaptationmentioning
confidence: 59%
See 3 more Smart Citations